The impact of obesity on secretion of adiponectin multimeric isoforms differs in visceral and subcutaneous adipose tissue - Kovacova, Z; Tencerova, M; Roussel, B; Wedellova, Z; Rossmeislova, L; Langin, D; Polak, J; Stich, V (International journal of obesity (2005), 2012)
OBJECTIVE: Hypoadiponectinemia observed in obesity is associated with insulin resistance, diabetes and atherosclerosis. The aim of the present study was to investigate secretion of adiponectin and its multimeric isoforms by explants derived from subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT) in obese and non-obese subjects. DESIGN: Paired samples of SAT and VAT and blood samples were obtained from 23 subjects (10 non-obese and 13 obese) undergoing elective abdominal surgery. Total adiponectin quantities and adiponectin isoforms were measured in conditioned media of explants derived from SAT and VAT using enzyme-linked immunosorbent assay and non-denaturing western blot, respectively. RESULTS: Total adiponectin plasma levels were lower in obese than in non-obese subjects (P<0.05). Secretion of total adiponectin in adipose tissue (AT) explants was lower in obese than in non-obese subjects in SAT (P<0.05) but not in VAT. In both, SAT and VAT, the most abundant isoform released into conditioned media was the high-molecular weight (HMW) form. Its relative proportion in relation to total adiponectin was higher in conditioned media of explants from both fat depots when compared with plasma (P<0.001). The proportion of secreted HMW vs total adiponectin was higher in VAT than in SAT explants in the group of non-obese individuals (49.3±3.1% in VAT vs 40.6±2.8% in SAT; P<0.01), whereas no difference between the two depots was found in obese subjects (46.2±3.0 % in VAT vs 46.0±2.4 % in SAT). CONCLUSION: Obesity is associated with the decrease of total adiponectin secretion in SAT. The profile of adiponectin isoforms secreted by SAT and VAT explants differs from that in plasma. Secretion of total adiponectin and HMW isoform of adiponectin are different in obese and non-obese subjects in relation to AT depot.
Keywords: nitrobřišní tuk; Insulin Resistance; adiponektin; Protein Isoforms; Male; inzulinová rezistence; Obesity; ateroskleróza; obezita; Adult; Diabetes Mellitus, Type 2; dospělí; mužské pohlaví; protein - isoformy; diabetes mellitus 2. typu; ELISA; Intra-Abdominal Fat; podkožní tuk; Enzyme-Linked Immunosorbent Assay; lidé; ženské pohlaví; Atherosclerosis; Humans; Subcutaneous Fat; Adiponectin; Female; lidé středního věku; Middle Aged